Opinions and practices of medical specialists concerning medical genetic services at the Pietersburg and Mankweng academic teaching hospitals in the Limpopo Province - Scholtz, Kathrine (Department of Clinical Laboratory Sciences, 2024)
Globally, approximately 7.9 million children are born annually with a genetic or partially genetic condition, with an estimated 3.3 million children under the age of five dying because of a serious congenital disorder (World Health Organization & March of Dimes, 2006). Early diagnosis and intervention through screening strategies, either during antenatal care or at birth, and access to proper treatment and health care can save the life of a child with a serious and life-threatening disability. Based on the National Department of Health Human Genetics Policy guidelines (2001), the Limpopo province would require 12 full-time medical geneticists (two per 1 million people), 48 genetic counsellors (four per medical geneticist) and 60 medical scientists (five per medical geneticist). To date, however, no medical geneticist or genetic counsellor posts have been created in the province and the provincial National Health Laboratory Service does not have a genetics diagnostic laboratory. Thus, there are currently no medical genetic services available or outreach programmes within either the public or private healthcare systems in Limpopo. Any patients requiring medical genetic services are referred to out-of-province services in Gauteng. The aim of this study was to canvas the opinions and shed light on the practices of medical specialists at the Pietersburg/Mankweng Hospital Complex in Limpopo with regard to medical genetic services, and whether there is a perceived need for or benefit of locally available medical genetic services. METHODS This study employed a mixed methods approach comprising a survey questionnaire (Phase 1), followed by semi-structured follow-up interviews (Phase 2) based on questions related to the aims and objectives of this study. The survey questionnaire was an online questionnaire consisting of thirty-six questions posed to determine the demographics, education, knowledge, referral patterns and opinions about comprehensive medical genetic services of the participants. The sample population consisted of 56 medical specialists from the departments of Family Medicine; Internal Medicine; Obstetrics and Gynaecology; Paediatrics and Child Health; and Surgery. A total of 32 responses were received. Results for this phase of the study were analysed using descriptive statistics. Semi-structured one-to-one interviews with open-ended questions were used to collect data for Phase 2. A total of 11 medical specialists were interviewed. Participant interviews were recorded and transcribed verbatim. The data were analysed using a thematic data analysis approach. RESULTS Results from Phase 1 showed that 44% of participants self-reported their genetics knowledge as fair; 41% felt somewhat comfortable discussing genetic information and risks with patients; and 44% felt that they were somewhat confident in their knowledge of available genetic tests and testing options. All participants were of the opinion that genetic counselling and genetic testing services are a necessity in the province, while 97% of the respondents felt that local access to medical geneticists was a necessity. While most medical specialists (88%) reported having treated patients in the past 12 months who would have benefitted from seeing a medical geneticist, only 13% reported referring these patients to a medical geneticist. Similarly, 81% of medical specialists indicated that they had seen patients or families in the past 12 months who would have benefitted from a genetic counselling service, however, only 28% had referred patients to such a service. With regard to genetic testing services, 94% of medical specialists reported seeing patients in the past 12 months who would have benefitted from genetic testing, and 50% of the respondents had sent samples for genetic testing. Results from the semi-structured one-to-one interviews highlighted the current lack of capacity, knowledge and resources available locally in Limpopo, and the challenges faced by patients when utilising out-of-province services in terms of social and financial costs, thus creating barriers to accessing comprehensive medical genetic services. Results also showed a perceived need for and benefit of locally available medical genetic services in the province to be able to provide comprehensive care to patients. CONCLUSIONS While there is a clear benefit and need for comprehensive medical genetic services in Limpopo, a cost-effective and clearly thought-out strategy needs to be established that does not place strain on an already overburdened and under-resourced provincial public healthcare system.